Correlation between magnetic and electric properties of La0.5Ca0.3Ag0.2MnO3 based on critical behavior of resistivity. Issue 8 (June 2016) - Smari, M.; Hamdi, R.; Dhahri, E.; Hlil, E.K.; Bessais, L.
Abstract: The relationship between electrical and magnetic properties of manganites has been traced through the analysis of temperature dependence of the La0.5 Ca0.3 Ag0.2 MnO3 resistivity. The measurement of resistivity versus temperature ρ ( T ) of the sample shows a paramagnetic semiconductor-ferromagnetic metallic transition at T = T MS . The application of magnetic field increases the T MS value and reduces the resistivity of the compound. The estimated critical exponents are ( β =0.273±0.01; γ = 1.074±0.02 and α =0.456). The values of these exponents obtained from resistivity are very close to them predicted by the tri-critical mean-field model. These results are in good agreement with the analysis of critical exponents from magnetization measurements. The electrical resistivity was fitted with the phenomenological percolation model, which is based on the phase segregation of ferromagnetic metallic clusters and paramagnetic semiconductor regions. So, we found that the estimated results are in adequate accordance with experimental data.